High genetic gains in wood volume and fecundity can be both achieved by direct selection in half-sib families of Pinus yunnanensis Franch - Chengjie Gao; Zhongmu Li; Jin Li; Kai Cui (Annals of Forest Science)
Abstract Key message This study demonstrates the potential of Pinus yunnanensis Franch. for multi-trait selection in breeding programs, highlighting positive co-variation of growth traits with fecundity, trunk straightness, and crown health in 16-year-old progenies. Integrated trait selection could enhance wood productivity and seed yield, supporting both commercial and ecological goals in reforestation efforts. Context The genetic improvement of P. yunnanensis, a species widely used for reforestation in Southwest China, is essential due to its economic importance and adaptability to harsh environments. Despite its extensive use, studies on mature trees are limited, particularly in multi-trait selection involving fecundity and trunk quality. Aims This study aimed to characterize phenotypic variation among and within provenances of P. yunnanensis, explore relationships among key traits, and evaluate the feasibility of joint selection for growth, fecundity, and trunk straightness. Methods We evaluated nine phenotypic traits in 3467 plus-tree progenies from six provenances in a common garden setting. Using structural equation modeling and “random forest” analysis, we identified key predictors of cone production and trunk straightness and assessed trait interrelationships. Results Significant phenotypic variations were observed among and within provenances of P. yunnanensis, with intra-provenance variation accounting for most of the total variation. Notably, 16.2% of trees exhibited twisted trunks, leading to a 14.9% decrease in wood volume compared to trees with straight trunks. The top 20% of individuals contributed 87.8% of total cone production, indicating substantial variation in fecundity. Growth, crown size, and crown health positively correlated with fecundity and trunk straightness, with tree height and diameter being the most important predictors. Both pairwise and multivariate analyses revealed significant and positive relationships among growth, fecundity, and crown health, suggesting high potential for multi-trait selection. Conclusion This study supports the feasibility of combined selection to optimize wood productivity, cone production, and crown health in breeding programs. These findings provide a valuable foundation for refining P. yunnanensis breeding strategies that meet the dual demands of economic utility and environmental adaptation in a changing climate.